Academic procrastination and negative emotions in the post-epidemic ERA: Life autonomy as a mediator and psychological resilience as a moderator - Cai, Xuan; Nawal, Ayesha; Rehman, Asad Ur; Sabir, Raja Irfan (Edelweiss Applied Science and Technology, 2026)
This study examines the mechanisms through which academic procrastination affects negative emotions among college students in the post-pandemic era, focusing on the mediating role of life autonomy and the moderating role of psychological resilience. A cross-sectional survey was conducted with 776 students from three Chinese universities, who completed measures of academic procrastination, negative emotions, life autonomy, and psychological resilience. Data were analyzed using mediated and moderated mediation models. The results showed that: (1) academic procrastination was positively associated with negative emotions; (2) life autonomy partially mediated this relationship—higher procrastination predicted lower life autonomy, which in turn predicted more negative emotions; and (3) psychological resilience moderated both the link between procrastination and life autonomy and the link between life autonomy and negative emotions. Specifically, higher resilience weakened the negative effect of procrastination on autonomy, while strengthening the protective effect of autonomy against negative emotions. These findings clarify how procrastination influences emotional well-being and highlight the importance of fostering life autonomy and psychological resilience in students. Practically, interventions aimed at reducing procrastination and improving emotional adjustment should incorporate strategies to enhance students’ sense of autonomy and resilience.